Heltens teleologiske potentiale - Anita Holm Riis (Akademisk Kvarter, 2020)
Heroes can be of many types, and they can have many functions. A common trait that they all share, however, is that they represent an ideal for their followers. Ideals can serve as a driving force in people’s lives and help foster individual development. The current article examines the teleological potential of heroes and its impact on individuals’ life goals. The perspective of the article is philosophical, focussing predominantly on Gadamer’s philosophical hermeneutics. From this perspective, the paper explores how heroes can impact their followers to make life-changing decisions. The article therefore includes an analysis of how heroes affect the interplay between their followers’ past and future. The questions of history and culture, including socialization and social heritage, also form an important part of the discussion.